Evaluation of Papaya (Carica papaya L.) Seed Oil's α-Linolenic Acid and Linoleic Acid Compounds in-Silico as Antidiabetic Agents Against PPAR-γ - Kadar Ismah; Yanulia Handayani; Claudia Dinda Safitri (LPPM Akafarma Sunan Giri Ponorogo, 2026)
Despite it’s widespread usage in medical practice, conventional medicine is thought to cause unfavorable pharmacological reactions in the body. This is a therapy issue that is getting worse every year, particularly for people with diabetes mellitus. This study used pre-experimental computational techniques based on traditional Chinese medicine to offer a safer alternative therapy. Determining if substances in papaya seeds (Carica papaya L.) are effective against the PPAR-γ receptor is the goal of this study. The chemicals α-linolenic acid and linoleic acid served as test ligands in this study, while rosiglitazone was utilized as a positive control to measure binding affinity using molecular docking with Autodock Tools 4 software. By getting an RMSD value of 1,110 Å, the study's findings demonstrated that the validation procedure had satisfied the requirements. Papaya seeds (Carica papaya L) contain active chemicals that may have antidiabetic properties. Of these, α-linolenic acid had a stronger affinity (docking score of -6,82) than linoleic acid (docking score of -6,07). Each compound's highest score is known as the docking score. The SPSS paired T test was then used to evaluate the results. Data analysis using the paired T test reveals that there is a significant difference between the binding activity values of α-linolenic acid and linoleic acid because the p value is less than 0.05. Based on data interpretation, the binding activity values of α-linolenic acid and linoleic acid show that the data is normally distributed because the p value is >0.05..